Obstetric violence and its impact on women's lives: An integrative review (Research, Society and Development, 2021)
The objective was to analyze the scientific evidence on the consequences of obstetric violence in women's lives during pregnancy. An integrative literature review study was conducted by searching the databases of the Virtual Health Library (VHL), SCIELO, LILACS, BDENF, with the following descriptors present in DECS: "Violence"; "Obstetrics"; "Women's health". 1371 articles were selected in total, then the inclusion criteria were applied and 218 were selected for reading the titles and abstracts. After this reading were selected 13 articles that met the research objective to compose the work. The results of the study showed that socioeconomic factors, fear, insecurity, lack of information about their rights during pregnancy and puerperium. We conclude that pregnant women need to know and demand that their rights and decisions be respected during pregnancy. Thus, it is necessary the training and empathy of health professionals in addition to the implementation of strategies to positively change this scenario.